FRI0601 The nature and extent of data items collected across european pregnancy registers – first results of the european network of pregnancy registers in rheumatology (EUNEP). (12th June 2018) - Meissner, Y.; Strangfeld, A.; Costedoat-Chalumeau, N.; Förger, F.; Molto, A.; Wallenius, M.; Fischer-Betz, R.
Abstract : Background: There is a high unmet need of robust data on the outcomes of pregnancies and drug safety in various inflammatory rheumatic diseases (IRD). The aims of the European Network of Pregnancy Registers in Rheumatology (EuNeP) are to bring together experts who run pregnancy registers, to define a core data set and to perform concerted data analyses. Objectives: To describe data items collected in existing multicentre European pregnancy registers in rheumatology. Methods: A comprehensive survey on details of the registers was performed encompassing patient enrolment, inclusion criteria, demographics, disease specific and general outcomes, medical treatment, course and outcome of pregnancy and outcomes of the child. Free text answers were possible for all questions. Questionnaires were sent to the principle investigator(s) of the participating studies. The completed questionnaires were reviewed, and responses were evaluated descriptively. Only data items collected during pregnancy are shown. Results: The following registers are involved in the collaboration: EGR2 (France), RePreg (Switzerland), REVNATUS (Norway) and Rhekiss (Germany). All registers collect data prospectively and nationwide. Patients can be included before pregnancy (child wish) or during pregnancy in all registers, and in RePreg also up to week 8 postpartal. Enrolment during pregnancy is possible up to gestation week 12 or thereafter in some specific cases (EGR2), week 20 (Rhekiss) or during complete pregnancy (RePreg and REVNATUS). All registers capture data via IT-based systems, REVNATUS documented on paper until 2016. During pregnancy, data is reported once every trimester by physicians and patients. Current figures, baseline characteristics and included IRD are presented in the table. Most of the data items that are independent of the underlying IRD are collected by all registers (figure 1). However, there are differences in the way data is collected and in the level of details. Conclusions: Although the registers in this collaboration have similar designs, we found considerable differences in data items collected. In particular, the level of details of documented data and the information on disease-specific characteristics varied. Harmonisation of data collected in pregnancy registers would facilitate collaborative analysis. Acknowledgements: This work was supported by a research grant from FOREUM Foundation for Research in Rheumatology. Disclosure of Interest: Y. Meissner: None declared, A. Strangfeld: None declared, N. Costedoat-Chalumeau: None declared, F. Förger Grant/research support from: UCB Pharma, Speakers bureau: Mepha, Roche, UCB Pharma, A. Molto: None declared, M. Wallenius: None declared, R. Fischer-Betz: None declared